2023
DOI: 10.3389/fphys.2023.1109754
|View full text |Cite
|
Sign up to set email alerts
|

Maternal opioids age-dependently impair neonatal respiratory control networks

Abstract: Infants exposed to opioids in utero are an increasing clinical population and these infants are often diagnosed with Neonatal Abstinence Syndrome (NAS). Infants with NAS have diverse negative health consequences, including respiratory distress. However, many factors contribute to NAS, confounding the ability to understand how maternal opioids directly impact the neonatal respiratory system. Breathing is controlled centrally by respiratory networks in the brainstem and spinal cord, but the impact of maternal op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 119 publications
(221 reference statements)
0
0
0
Order By: Relevance
“…Mechanical ventilation increased the expression of NLRP3 mRNA in alveolar macrophages and caused lung inflammation dependent on NLRP3 inflammatory bodies [ 28 , 29 ]. High inspiratory airflow during mechanical ventilation causes shear stress along airway and alveolar surfaces, leading to deformation of lung tissue and bronchial cells and the release of substances that promote scarring and inflammation [ 30 , 31 ]. The current study showed that using the ventilation mode with prolonged inspiratory time and an optimized inspiratory flow rate led to a significant decrease in inflammatory cells, such as the WBC count, in the blood of post-surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation increased the expression of NLRP3 mRNA in alveolar macrophages and caused lung inflammation dependent on NLRP3 inflammatory bodies [ 28 , 29 ]. High inspiratory airflow during mechanical ventilation causes shear stress along airway and alveolar surfaces, leading to deformation of lung tissue and bronchial cells and the release of substances that promote scarring and inflammation [ 30 , 31 ]. The current study showed that using the ventilation mode with prolonged inspiratory time and an optimized inspiratory flow rate led to a significant decrease in inflammatory cells, such as the WBC count, in the blood of post-surgery patients.…”
Section: Discussionmentioning
confidence: 99%